Na+/Ca2+ Exchanger Inhibitors Inhibit Neurite Outgrowth in PC12 Cells - Toru Oda; Toshiaki Kume; Yasuhiko Izumi; Kumatoshi Ishihara; Hachiro Sugmimoto; Akinori Akaike (Elsevier, 2011)
Abstract.: To elucidate the role of Na+/Ca2+ exchanger (NCX) in neurite outgrowth, we investigated the effects of NCX inhibitors on neurite outgrowth in PC12 cells. KB-R7943 and 3',4'dichlorobenzamil, NCX inhibitors, inhibited the neurite outgrowth caused by nerve growth factor (NGF). NCX inhibitors inhibited the neurite outgrowth caused by dibutylyl cAMP, which rapidly reorganizes the cytoskeleton. KB-R7943 inhibited the neurite outgrowth caused by Y-27632, an inhibitor of Rho kinase (ROCK) that regulates actin. However, NCX inhibitors did not inhibit NGF-induced phosphorylation of extracellular signal-regulated kinase. These results suggest that NCX inhibitor affects downstream of the Rho-ROCK signal transduction pathways in neurite outgrowth. Keywords:: Na+/Ca2+ exchanger (NCX), neurite outgrowth, PC12